Tuning the Polarity of Antibiotic-Cy5 Conjugates Enables Highly Selective Labeling of Binding Sites - Graßl, Fabian; Konrad, Maike; Krüll, Jasmin; Pezerovic, Azra; Zähnle, Leon; Burkovski, Andreas; Heinrich, Markus (Chemistry - A European Journal, 2023)
Multidrug-resistant bacteria pose a major threat to global health, even as newly introduced antibiotics continue to lose their therapeutic value. Against this background, deeper insights into bacterial interaction with antibiotic drugs are urgently required, whereas fluorescently labeled drug conjugates can serve as highly valuable tools. Herein, the preparation and biological evaluation of 13 new fluorescent antibiotic-Cy5 dye conjugates is described, in which the tuning of the polarity of the Cy5 dye proved to be a key element to achieve highly favorable properties for various fields of application.
CRIS-Team Scopus Importer:2023-07-28
Keywords: antibiotics; cyanines; dye conjugates; fluorescence; microscopy